Mimesis among expressional Algerian writers quest for identity between unease and belonging: Study of L’Opium et le bâton (Mammeri, 1965) - Abdelkader BEHTANE (Department of French Language Education, Universitas Pendidikan Indonesia, 2022)
RÉSUMÉ. L'étude de la psyché et la reproduction des mœurs (éthopée) ont de tout temps inspiré les écrivains. Ainsi, la représentation littéraire (mimesis), basée sur la description de lieux ou de personnages, permet une meilleure compréhension de l'être humain et de son environnement. À travers l'analyse de contenu d'extraits du roman L'opium et le bâton de Mammeri (1965), l'étude vise la quête identitaire individuelle et groupale, la quête d'appartenance et de malaise conjugués dans les revendications du peuple algérien. Les résultats montrent que la mimesis est utilisée pour interroger l'identité et permet de mieux comprendre la cruauté que l'algérien vit. En conclusion, à cause de leur ambition, les Algériens subissent les brimades des colons : retrouvés dans l'absurde ; face à l'opium qui déraisonne et le bâton qui châtie la volonté. Or, quand le meneur s'engage dans l'engrenage de deux comportements aberrants : la perversité « raisonne » et rend l'identité illusoire. Mots-clés : appartenance, malaise, mimesis, quête identitaire, représentation, roman algérien.ABSTRACT. The study of the psyche and the reproduction of customs (ethopoeia) have always inspired writers. Thus, literary representation (mimesis), based on the description of places or characters, allows a better understanding of the human being and his environment. Through the content analysis of excerpts from Mammeri's novel L'opium et le bâton (1965), the study focuses on the quest for individual and group identity, the quest for belonging and the unease combined in the claims of the Algerian people. The findings show that mimesis is used to interrogate identity and allows for a better understanding of the cruelty that the Algerian experiences. In conclusion, because of their ambition, the Algerians suffer the bullying of the colonists: found in the absurd; faced with the opium that derails and the stick that punishes the will. But when the leader engages in the spiral of two aberrant behaviours: perversity 'reasons' and makes identity illusory. Keywords: Algerian novel, belonging, identity quest, mimesis, representation, unease,